Impact of COVID-19 on Acute Coronary Syndrome: An Examination of Mortality and Demographic Factors - Dian Primadia Putri (Archives of The Medicine and Case Reports, 2025)
The COVID-19 pandemic has significantly impacted cardiovascular health, with acute coronary syndrome (ACS) emerging as a major concern. This study investigates the relationship between demographic characteristics, mortality rates, and the incidence of ACS in COVID-19 patients. A retrospective study was conducted on a cohort of 68 patients diagnosed with both COVID-19 and ACS, admitted to a hospital in Medan between August 2020 and August 2021. Demographic data, COVID-19 severity, electrocardiogram (ECG) findings, and comorbid conditions were analyzed for their association with mortality. The mean age of the study participants was 58.2 years, with a male predominance (82.9%). The majority of patients experienced severe COVID-19 (62.9%), and the most common ECG finding was ST-elevation (62.9%). Hypertension was the most prevalent comorbidity (52.9%). Mortality was significantly associated with male gender (p=0.01) but not with COVID-19 severity, ECG findings, or comorbidities. In conclusion, male gender was identified as an independent predictor of mortality in COVID-19 patients with ACS. Further research is needed to elucidate the complex interplay of demographic factors, COVID-19, and ACS outcomes.